Plataforma digital para reservas de canchas sintéticas - Muro Espino, Luis Eduardo (2020)
Currently in Metropolitan Lima there are around 69 sports centers that offer seven synthetic soccer fields. One of the main problems, according to interviews with the administrators, is the working method with which they manage the reservations of the synthetic fields. As of right now, if someone were to make a reservation, a blackboard or a notebook is used, which has generated many inconveniences with the crossing of reservations, repetitive reservations and delays in listing. In addition, sometimes, this problem leads to the loss of corporate clients or companies.The proposed solution is aimed at administrators and athletes, who play football in synthetic grass. It consists of the creation of a platform that streamlines and improves the process of reserving a synthetic field in Metropolitan Lima. This will seek to reduce the risk of error on the part of administrators and, in addition, improve the traditional reservation method to a more efficient one. Likewise, it seeks to improve the experience of athletes by giving them easier access to a synthetic field from the comfort of their mobile phone. Currently, there are no similar proposals on the market that fulfill the same functions. However, there is a brand with a website and another with a mobile application. Those who, despite being in the market, still fail to position themselves or have a significant number of clients due to deficiencies in their platform. After having carried out market studies, through surveys of end users and interviews with administrators of sports centers, it was determined that there is an unmet demand and a high probability that people will use our application. In addition to this, there are market studies that indicate that the demand for the rental of synthetic fields will increase due to participation of the Peruvian Soccer Team. In order to confirm the viability of the project, a financial study was carried out and, through the media of VNA and TIR, the profitability of the project was determined